Radical Changes in Political Campaign Strategy Prabowo Subianto's in the 2024 Presidential Election Indonesia: - - Erik Ardi yanto (Ikatan Sarjana Komunikasi Indonesia, 2025)
The 2024 presidential election in Indonesia witnessed significant changes in the political campaign strategy of Prabowo Subianto, characterized by a radical departure from previous approaches. This research employs critical discourse analysis methods and documentation studies to analyze the transformative shifts in Prabowo's campaign tactics. The findings reveal a strategic rebranding of Prabowo's image, transitioning from a firm and temperamental figure to a more cheerful and humanistic persona. This rebranding was facilitated by the adoption of shallow political gimmicks, including